"Value" as Seen in Kofun Period Tomb Mounds: The Case of Roji Tomb, Fukuoka Prefecture - ONISHI, Tomokazu (Nihon Kokogaku(Journal of the Japanese Archaeological Association), 1996)
This paper approaches the system of "value", or what prehistoric people considered "valuable" or "significant", by examining correlations among several aspects of elite mortuary practices in fifth century Japan. These selected aspects are considered "significant" and "valuable" by contemporary archaeologists; if, however, an "important" aspect correlates statistically with other "important" aspects, it is possible to assume that people of the fifth century also considered these aspects important and valuable. The subjects I have adopted for testing hypotheses concerning the value system are types of haniwa clay objects and the positions where they stood on the surface of Roji Tomb, a keyhole-shaped tumulus in Fukuoka Prefecture, northern Kyushu, dated to the beginning of the fifth century. It is a widely accepted interpretation that people of the Kofun Period considered the circular portion of a keyhole tomb more important than the rest of the mound, because it contains the main burial chamber and is taller than the rest of the mound until the fifth century. It is also easy to imagine that locations on the mound surface closer to the main burial chamber were considered more important. In order to test these interpretations, I applied the concept of "degree of elaboration" to an analysis of haniwa clay objects. The higher the degree of elaboration, the more effort people put into the preparation of the object, and the greater the possibility that people considered the object more important than those with lower degrees of elaboration. Attributes of higher degrees of elaboration include a stepped rim (e.g. Fig. 1, No. 15) as opposed to a simple rim (e.g. Fig. 1, No. 1), a more abstract and advanced cylindrical shape (Fig. 23) as opposed to more a traditional pot shape (Figs. 1 and 2), and a narrower space between haniwa standing in line as opposed to a wider space. If the space was narrow, more haniwa were necessary for filling the same length of line, indicating more labor required. If the interpretation mentioned above is correct for the fifth century, then we can expect haniwa with higher degrees of elaboration to be found on the rear portion of the mound and particularly near the main burial chamber. The results of my statistical analysis clearly show that those with higher degrees of elaboration were placed on the round portion and particularly in an area close to the main burial chamber. This suggests that people in the fifth century indeed has a system of "value" in which the round portion of a keyhole tomb was considered more important than the rest of the mound.